Functionalization strategies of polymeric nanoparticles for drug delivery in Alzheimer’s disease: Current trends and future perspectives - La Barbera, Livia; Mauri, Emanuele; D’Amelio, Marcello; Gori, Manuele (Frontiers in Neuroscience, 2022)
Alzheimer’s disease (AD), the most common form of dementia, is a progressive and multifactorial neurodegenerative disorder whose primary causes are mostly unknown. Due to the increase in life expectancy of world population, including developing countries, AD, whose incidence rises dramatically with age, is at the forefront among neurodegenerative diseases. Moreover, a definitive cure is not yet within reach, imposing substantial medical and public health burdens at every latitude. Therefore, the effort to devise novel and effective therapeutic strategies is still of paramount importance. Genetic, functional, structural and biochemical studies all indicate that new and efficacious drug delivery strategies interfere at different levels with various cellular and molecular targets. Over the last few decades, therapeutic development of nanomedicine at preclinical stage has shown to progress at a fast pace, thus paving the way for its potential impact on human health in improving prevention, diagnosis, and treatment of age-related neurodegenerative disorders, including AD. Clinical translation of nano-based therapeutics, despite current limitations, may present important advantages and innovation to be exploited in the neuroscience field as well. In this state-of-the-art review article, we present the most promising applications of polymeric nanoparticle-mediated drug delivery for bypassing the blood-brain barrier of AD preclinical models and boost pharmacological safety and efficacy. In particular, novel strategic chemical functionalization of polymeric nanocarriers that could be successfully employed for treating AD are thoroughly described. Emphasis is also placed on nanotheranostics as both potential therapeutic and diagnostic tool for targeted treatments. Our review highlights the emerging role of nanomedicine in the management of AD, providing the readers with an overview of the nanostrategies currently available to develop future therapeutic applications against this chronic neurodegenerative disease.